A SINGLE-STAGE POSTERIOR APPROACH AND RIGID FIXATION FOR PREVENTING KYPHOSIS IN THE TREATMENT OF SPINAL TUBERCULOSIS - (:unkn) unknown (LIPPINCOTT-RAVEN PUBL, 1994)
Study Design. The authors employed a new mode of treatment for spinal tuberculosis consisting of single stage posterior instrumentation and fusion without anterior debridement. Ten patients were operated upon in this manner. Chemotherapy was instituted 2 weeks preoperatively and continued for a mean period of 11 months. Cotrel-Dubousset or a comparable system was used fixation. Objectives. Patients were followed for 3 monthly intervals with serial anteroposterior and lateral x-rays, erythrocyte sedimentation rate, physical examination, and patients' self reports. The mean follow up period was 24.2 months (range, 17-36 months). Methods. Measurement of kyphosis angle in the lateral x-ray view was used to evaluate treatment. Results. Only a 3.4-degrees mean loss of correction was observed over the follow-up period. All patients were satisfied. Conclusion. Our results show that posterior rigid fixation and chemotherapy provide satisfactory stabilization, reduce surgical morbidity, and prevent development of late kyphosis in selected patients with Pott's disease of the thoracolumbar spine.